RARE EARTH MATERIALS IN THE INDUSTRY OF UZBEKISTAN AND THEIR APPLICATION IN MECHANICAL ENGINEERING - Urinov Nasillo Fayzilloevich; Mahmudov Dilshodbek Bahodir ugli (Journals Park Publishing, 2025)
The demand for rare metals in high-technology industrial production determines their high cost on the global market. The article presents an example of the possibility of using rare-earth metals for coating cutting tool inserts in order to increase productivity.